Daun Binahong Sebagai Bakteriostatik - Widhowati, Dyah (VITEK : Bidang Kedokteran Hewan, 2023)
This study aims to determine the potential of binahong leaf extract (Anredera cordifolia) against Salmonella sp. This study used 5 treatments consisting of P(-) Blank Disk as negative control, P(+) chlorampenicol Disk as positive control, P1 binahong leaf extract concentration 60%, P2 binahong leaf extract concentration 80%, P3 binahong leaf extract concentration 100 %. The results of this study indicated that binahong leaf extract at concentrations of 60%, 80% and 100% had the potential to reduce the growth of Salmonella sp, due to the presence of quite a lot of antibacterial levels in binahong leaf extract. The antibacterial levels of binahong leaf extract include (1) Tannins (positive) (2) Saponins (moderately positive) (3) Falvonoids (weakly positive) (4) Steroids (weakly positive) (5) Alkaloids (positive) (6) Phenolics ( weak positive). Antibacterial content in the form of saponins, falvonoids, alkaloids, phenolics and tannins which are the causes of Binahong leaf extract being able to inhibit the growth of Salmonella sp on Muller Hinton Agar (MHA) media.